Tölur og mengi – Numbers and sets. A New Math textbook in Iceland in the 1960s - Bjarnadóttir, Kristín (NOMAD Nordic Studies in Mathematics Education, 2015)
Only few mathematics textbooks were developed in Icelandic during 1930–1966, and the model textbooks in use were originally developed in the 1920s. In 1966, Iceland was hit by an international school-mathematics reform movement, the New Math. The learning material, which was introduced at the arrival of the movement until the 1970s, was all of foreign origin except one textbook. The author of that textbook, denoted Tölur og mengi [Numbers and sets], was main actor in the introduction of the New Math, Guðmundur Arnlaugsson, duly supported by his colleague, Björn Bjarnason. In the paper, their way of introducing the new ideas and the methods they used will be described. Among their tools is the textbook which later influenced other mathematics textbooks for adolescents after the peak of the New Math wave.